2023
DOI: 10.3389/fpsyg.2022.952010
|View full text |Cite
|
Sign up to set email alerts
|

Why does frugality influence the recycling intention of waste materials?

Abstract: Waste recycling significantly impacts the sustainable development of society and the ecological environment, contributing to a vital role within the waste management hierarchy. This paper presents a research model that investigates the influence mechanism of consumers’ frugality on their recycling intentions. This study collected 420 valid samples to test the model with regression analysis. The empirical results show that consumers’ frugality exerts a direct and positive effect on their recycling intention. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
(61 reference statements)
1
1
0
Order By: Relevance
“…This relation highlights the duality of the self-regulated mindset as a motivation for recycling behavior (H2, H3a and H3b). Despite each variable's direction being corroborated by previous studies [42,48,54,61,64,69], the integration of these variables in our study represents a significant and novel finding. Frugal individuals tend to be goal-directed, planning and taking action to achieve their goals [81].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This relation highlights the duality of the self-regulated mindset as a motivation for recycling behavior (H2, H3a and H3b). Despite each variable's direction being corroborated by previous studies [42,48,54,61,64,69], the integration of these variables in our study represents a significant and novel finding. Frugal individuals tend to be goal-directed, planning and taking action to achieve their goals [81].…”
Section: Discussionsupporting
confidence: 65%
“…For example, research conducted by Lastovicka et al [17] found that frugality predicts resource-saving behaviors, including recycling. Ribeiro et al [42] and Wang et al [64] also found that frugality positively affects consumers' recycling intention and recycling behavior. Additionally, several studies that conceptualize frugality in terms of consumption habits, emphasizing the optimal utilization of assets and minimizing waste, have established a positive correlation between frugality, green consumption, and recycling [65].…”
Section: Frugality To Recycling Behaviormentioning
confidence: 96%